ACTIVATED CARBON PRODUCTION FROM TURF SOIL - SANI, SANI (Jurnal Teknik Kimia, 2011)
Indonesia is one of the country that proposed as a country tag has the world's largest peat, whilethe carbon content in peat is quite high, namely ± 60%. To increase the economical value of peat in amanner that is processed into activated carbon. This research aims to make activated carbon from thepeat soil and nutrient concentrations studied the influence of activators and activation times for the qualityactivated carbon produced. Raw materials used to make activated carbon is peat derived from centralKalimantan. H2SO4 solution is used as the activator. While Iod solution, a solution of potassium iodideand thiosulphate solution 0.1 N is used as active carbon absorbent testing agent. Set of variables: 550 0Ctemperature carbonization, carbonization time of 2 hours, peat, coal 40 mesh particle size , weight of 100grams of active carbon, the comparison of the char activator 1: 10 and the drying temperature is 120 0C.Carried out activator concentration are 5%, 10%, 15%, 20% and 25% and time of immersion / activationare 1, 1.5, 2, 2.5, 3 (h). Research results are measured from the active carbon absorbent rate of Iodinesolution. Best results absorbed rate measured as 21.88% were obtained in 20% H2SO4 concentration andactivation time of 2.5 hours.Key words: active carbon, peat, activator, carbonization, absorbent rate